2013
DOI: 10.3747/pdi.2012.00160
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Peritoneal Dialysis Catheter Insertion by a Nephrologist: A New, Simple, and Safe Technique

Abstract: ♦ Background: Insertion of the peritoneal dialysis (PD) catheter by a nephrologist has been encouraged by several studies. The ultimate goal is to provide safe, timely, and effective catheter insertion without an unduly long wait time or delay. The success of PD depends partly on the ease of catheter insertion. We developed a new technique for percutaneous PD catheter insertion by nephrologists. Our new technique, in addition to being easy, proved to be safe and to eliminate the need for the peel-away sheath. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…Our PD unit at King Fahd University Hospital is one of the most experienced in the Middle East with PD therapy. Importantly, we have developed a new technique in PD catheter insertion that made the rapid institution of PD much simpler than before . In our study, Physioneal was chosen as a potentially more physiologic dialysate as it limits the potential undesirable side effects of the lactate‐buffered solutions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our PD unit at King Fahd University Hospital is one of the most experienced in the Middle East with PD therapy. Importantly, we have developed a new technique in PD catheter insertion that made the rapid institution of PD much simpler than before . In our study, Physioneal was chosen as a potentially more physiologic dialysate as it limits the potential undesirable side effects of the lactate‐buffered solutions .…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol indicated that treatment should be given continuously with a change of membrane every 48 h. In patients randomized to TPD, a flexible double cuff Tenckhoff catheter (Flex‐Neck Classic Peritoneal Dialysis Catheter, Merit Medical Systems, Inc. South Jordan, UT, USA) was used. All PD catheters were inserted by trained nephrologists using Al‐Hwiesh technique (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, percutaneous catheter insertion with or without image guidance may be considered for peritoneal access 29,30 . Although experience with percutaneous placement is not as widespread, it is a technique that can be performed at bedside or in the radiology suite by surgeons, interventional radiologists, or interventional nephrologists who have learnt these techniques for the first time during the COVID-19…”
Section: Concerns Regarding Acute Pd and Patient Selectionmentioning
confidence: 99%
“…In contrast, retrospective studies have reported incidences of 20.2% using blind percutaneous insertion and 27.1% using laparoscopy 20,21 . In some reports, incision and tunnel infection have occurred regardless of technique (surgical laparotomy, percutaneous puncture, or laparoscopic catheterization) 5,20,22 . We believe that our new PD catheterization method has inherent advantages in this regard.…”
Section: Discussionmentioning
confidence: 84%
“…20,21 In some reports, incision and tunnel infection have occurred regardless of technique (surgical laparotomy, percutaneous puncture, or laparoscopic catheterization). 5,20,22 We believe that our new PD catheterization method has inherent advantages in this regard.…”
Section: Discussionmentioning
confidence: 99%